أثر الحوار في التصوير الفني في قصص الانبياء قصتي ابراهيم وموسى عليهما السلام - سلمى بن ليفة (university of eloued جامعة الوادي, 2025)
هذا البحث المرسوم بعنوان كيف ساهم الحوار في بناء التصوير الفني في قصتي إبراهيم وموسى عليهما السلام ؟ وما أبعاده البلاغية والدلالية في إبراز المعاني والتأثير النفسي ويهدف إلى الإجابة على الإشكالية التالية: كيف صورت لنا الآيات القرآنية لمشاهد الحوار في قصتي إبراهيم وموسى عليهما السلام؟ وللإجابة على هذه الإشكالية يستهل البحث بمفاهيم عامة، حول الحوار، وأهميته، والتصوير الفني ومظاهره، وفي الجانب التطبيقي، قدمت نماذج لمشاهد الحوار وبينت تصورها فنيا مدعمة بالتفاسير العلمية واتبعت المنهج الوصفي التحليلي وتوصلت الى عدة نتائج من أبرزها صورت لنا الآيات القرآنية في قصتي إبراهيم وموسى عليهما السلام بأسلوب دعوية وحكم بليغة وإثبات العقيدة وصراع بين الحق والباطل مما يجعل هذه القصص دورس خالدة في حياة المسلم. This research,The Effect of Dialogue on Artistic Depiction in the Stories of the Prophets, the Stories of Abraham and Moses as an Example, aims to answer the following problem: How were the Qur’anic verses depicted for us the scenes of dialogue in the stories of Abraham and Moses, peace be upon them? To answer this problem, the research begins with general concepts about dialogue, its importance, artistic photography and its manifestations, and in the applied aspect I presented examples of dialogue scenes and demonstrated their artistic conception, supported by scientific interpretations.I followed the descriptive and analytical approach and reached several results, the most prominent of which is that the Qur’anic verses in the stories of Abraham and Moses, peace be upon them, were depicted to us in a style of advocacy, eloquent wisdom, proof of belief, and a struggle between truth and falsehood, which makes these stories lessons.Eternal in the life of a Muslim
مذكرة ماستر
Keywords: الحوار التصوير الفني قصص الأنبياء Dialogue Artistic Photography Stories of the Prophets